Studies of the in vitro cytotoxic, antioxidant, lipase inhibitory and antimicrobial activities of selected Thai medicinal plants - Kaewpiboon Chutima; Lirdprapamongkol Kriengsak; Srisomsap Chantragan; Winayanuwattikun Pakorn; Yongvanich Tikamporn; Puwaprisirisan Preecha; Svasti Jisnuson; Assavalapsakul Wanchai (BMC, 2012)
Abstract Background Traditional folk medicinal plants have recently become popular and are widely used for primary health care. Since Thailand has a great diversity of indigenous (medicinal) plant species, this research investigated 52 traditionally used species of Thai medicinal plants for their in vitro cytotoxic, antioxidant, lipase inhibitory and antimicrobial activities. Methods The 55 dried samples, derived from the medicinally used parts of the 52 plant species were sequentially extracted by hexane, dichloromethane, ethanol and water. These 220 extracts were then screened for in vitro (i) cytotoxicity against four cell lines, derived from human lung (A549), breast (MDA-MB-231), cervical (KB3-1) and colon (SW480) cancers, using the MTT cytotoxicity assay; (ii) antioxidant activity, analyzed by measuring the scavenging activity of DPPH radicals; (iii) lipase inhibitory activity, determined from the hydrolytic reaction of p-nitrophenyllaurate with pancreatic lipase; and (iv) antimicrobial activity against three Gram-positive and two Gram-negative bacteria species plus one strain of yeast using the disc-diffusion method and determination of the minimum inhibitory concentration by the broth micro-dilution assay. Results The crude dichloromethane and/or ethanol extracts from four plant species showed an effective in vitro cytotoxic activity against the human cancer cell lines that was broadly similar to that of the specific chemotherapy drugs (etoposide, doxorubicin, vinblastine and oxaliplatin). In particular, this is the first report of the strong in vitro cytotoxic activity of Bauhinia strychnifolia vines. The tested tissue parts of only six plant species (Allium sativum, Cocoloba uvifera, Dolichandrone spathacea, Lumnitzera littorea, Sonneratia alba and Sonneratia caseolaris) showed promising potential antioxidant activity, whereas lipase inhibitory activity was only found in the ethanol extract from Coscinum fenestratum and this was weak at 17-fold lower than Orlistat, a known lipase inhibitor. The highest antimicrobial activity was observed in the extracts from S. alba and S. caseolaris against Pseudomonas aeruginosa and Candida albicans, respectively. Conclusion The Thai medicinal plant B. strychnifolia is first reported to exert strong in vitro cytotoxic activities against human cancer cell lines and warrants further enrichment and characterization. The broad spectrum of the biological activities from the studied plant extracts can be applied as the guideline for the selection of Thai medicinal plant species for further pharmacological and phytochemical investigations.